2018
DOI: 10.31235/osf.io/vz5pk
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Social conditions of outstanding contributions to computer science : a prosopography of Turing Award laureates (1966-2016)

Abstract: The Turing Award, commonly described as computer science's highest award and equivalent of the Nobel prize in that discipline, has now been awarded for half a century. In the following, we describe the social regularities that underlie and the conditions that embed these high achievements in computer science innovation. We find, contrary to a meritocratic ideal of one's only abilities determining success or recognition within sciences, that several characteristics of scientists, exogenous and non-exogenous ali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 3 publications
(3 reference statements)
0
2
0
Order By: Relevance
“…Compared to Nobel Prize, the work focused on the Turing Award is limited. From a sociology study, Akmut (2018) concluded that place of birth, nationality, gender, social background, race and networks play a role in making Turing Award laureates. Xia et al (2020) proposed a metric named "Turing Number" to measure the distance between scholars and Turing Award laureates, as a new way to construct a scientific collaboration network centered around the laureates.…”
Section: Background and Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…Compared to Nobel Prize, the work focused on the Turing Award is limited. From a sociology study, Akmut (2018) concluded that place of birth, nationality, gender, social background, race and networks play a role in making Turing Award laureates. Xia et al (2020) proposed a metric named "Turing Number" to measure the distance between scholars and Turing Award laureates, as a new way to construct a scientific collaboration network centered around the laureates.…”
Section: Background and Related Workmentioning
confidence: 99%
“…Can we find some rules or best practices to promote further development of computer science? These questions prompt people to study from outside computer science itself, e.g., from the perspective of history and the sociology of science (Akmut 2018). In this study, we are analyzing from the * The two authors contributed equally.…”
Section: Introductionmentioning
confidence: 99%